Virtual occlusion in orthognathic surgery. Issue 9 (September 2021) - Baan, F.; van Meggelen, E.M.; Verhulst, A.C.; Bruggink, R.; Xi, T.; Maal, T.J.J.
Abstract: The aim of this retrospective study was to determine whether a virtually created occlusion is as accurate as a conventionally created occlusion. Seventeen orthognathic patients were included in the study, which was conducted in a university clinic. Plaster cast models were obtained and digitized. Two experienced observers created the conventional (gold standard) and virtual occlusion to assess inter-observer variability. One observer created the conventional and virtual occlusion a second time to assess the intra-observer variability. The criterion for accepting the virtual occlusion was that the difference between the gold standard and the virtual occlusion was not larger than the intra-observer variability for the gold standard. A non-parametric Kruskal–Wallis H test was performed to detect statistically significant differences between the intra- and inter-observer groups for both the conventional and virtual occlusion. No statistically significant differences were found between the different groups. The difference between the conventional and virtual occlusion group was 0.20 mm larger than the intra-observer variability of the gold standard. The virtual occlusion tool presented here can be utilized in daily clinical practice and makes the use of physical dental models redundant.